Clinical research progress on the relationship between vitamin D and glucose metabolism disorders - Yin CHEN; Zhitian ZHANG; Jiaojiao LIU; Hongmei YAN; Shanshan GUO (Zhongguo Linchuang Yixue, 2025)
Approximately 10% of the global adult population has diabetes, with accumulating evidence linking suboptimal vitamin D levels to an increased risk of type 2 diabetes and its complications. Current clinical studies suggest that vitamin D supplementation may enhance insulin sensitivity and improve glycemic control, prompting significant interest in its potential as a therapeutic intervention. However, further high-quality, large-scale randomized controlled trials are required to validate its efficacy in glucose metabolism regulation and clarify the underlying molecular mechanisms. These investigations will provide critical evidence to inform precision medicine approaches for diabetes prevention and management.